Strategi Promosi Dalam Meningkatkan Kunjungan Museum KotaGede Intro Living Museum - Kartika Sari Yudaninggar; Dwiyana Rahma Fitri; Riski Damastuti (Prisani Cendekia Institute, 2023)
Kotagede Museum Intro Living Museum is one of the museums in Yogyakarta and is still considered a new museum. This research aims to discover how promotional strategies can increase the number of Kotagede Intro Living Museum visits. This research uses a qualitative descriptive research design with a constructivist paradigm. The technique used to determine research subjects is purposive sampling; data is collected from interviews, observations, and documentation, then presented as a discussion. Researchers used four sources from museum managers and three sources from museum visitors. From the research that has been carried out, the management of the Kotagede Museum has carried out good promotional strategies. The promotional strategy follows the elements contained in the promotion mix: advertising, sales promotion, public relations, face-to-face selling, and direct marketing. Marketing). The most influential strategy currently is internet advertising, especially on the museum's Instagram social media account @museumkotagede. In this way, the strategy to increase museum visits should continue to be carried out with various elements contained in the promotional mix so that the promotional strategy carried out can be more effective.